Application of Good Governance Principles at Sampir Village Office, Taliwang District, West Sumbawa Regency - Zamakhsyari, Nuari; Yamin, Ahmad; Suparman, Suparman (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The application of the principles of transparency, accountability and community participation in the context of good governance at the Sampir Village Office, Taliwang District, is a crucial aspect for improving the quality of public services. Good governance is the main basis for carrying out government duties that are oriented towards openness, responsibility and active involvement of the community. Therefore, this research aims to explore the extent to which these principles are implemented in sub-district offices and identify factors that hinder their implementation.This research uses a survey method to achieve its objectives. Data collection techniques involve interviews, observations and structured observations, which are arranged based on research variables. Information was obtained from selected respondents who had direct involvement in the Sampir Village Office, Taliwang District. Apart from that, the author also refers to various relevant literature sources to gain a deeper understanding of the research topic.The application of good governance principles, especially transparency, accountability and community participation, can make a positive contribution to improving the quality of service at the Sampir Village Office, Taliwang District. However, several obstacles were also identified, including problems within the service team, management of staff assignments, lack of coordination between staff, and lack of clarity in service times.This research concludes that the application of good governance principles is an effective step to increase the efficiency and effectiveness of public services at the sub-district level. However, improvement and improvement efforts are still needed to overcome the obstacles faced, such as improving team management, clearer division of tasks, increasing coordination between staff, and clarifying service times. Implementation of good governance principles is the key to achieving better governance in providing services to the community..